Exploring the Nutritional Ecology of Stunting in a Village-Based Tourism: Towards Stunting-Free Tourism Industry in Lombok - Siti Ruqayyah; Baiq Santi Rengganis; Akhmad Azmiardi (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Stunting has still been a primary target of the worldwide health agenda—external determinants such as economic, demographic, and environmental factors are the major causes. From now on, both external and internal factors are referred to as "nutritional ecologies". This research aims to examine the nutritional ecologies of stunting in a village-based tourist destination, namely Sigerongan Village of West Lombok, through several steps – (1) identifying factors leading to stunting in the village, (2) formulating the primary drive of the prevalence of stunting, (3) developing a model of free-stunting village-based tourism, and (4) proposing social and cultural interventions to tackle the stunting issue. This longitudinal study employs several methods, especially prototypical research and reflective analysis. The data analyses were chi-square and fisher test exact test to examine the relationships among variables. The intervention model is generated and named "Dewi Santi," which is the acronym for "Desa Wisata Tahan Stunting" or "Stunting-Free Village-based Tourism" model. The complex nature of stunting requires an ecological approach that includes nutritional ecologies so that it is translatable into practice and can be rooted in a particular culture whereby the prevalence is high. However, this study's limitation lies in its design, which was only tried to examine the nutritional problem, and research design can be broadened and varied for future studies.